PEMANFAATAN MEDIA CANVA UNTUK MENINGKATKAN PEMAHAMAN KONSEP MENGUKUR SUDUT PADA SISWA KELAS V SDN 15 SIKAKAP - Silviana Evi Vitriani Taileleu; Syafri Ahmad; Salmaini Salmaini (STKIP Subang, 2025)
This study explores the development of Canva-based learning media to enhance Grade 4 students’ understanding of equivalent fractions in elementary mathematics. The research is grounded in the increasing demand for digital, visual, and interactive learning resources that can strengthen conceptual comprehension in the digital era. Using a descriptive qualitative design supported by stages of analysis, design, development, implementation, and evaluation, this study systematically documents the creation and classroom application of Canva-based fraction materials. Data were gathered through observation, documentation, and limited user testing involving teachers and students. The findings indicate that Canva media provides clearer visual representations, strengthens conceptual links between symbolic and visual forms of equivalent fractions, and increases student engagement during learning activities. Teachers also reported that the media facilitates explanation and reduces common misconceptions. Overall, the study concludes that Canva is an effective and accessible tool for developing mathematics learning materials that support conceptual clarity, engagement, and independent learning among elementary students.